Human Amniotic Membrane and Curcuma Longa– Derived Gel for the Treatment of Burn Injuries in a Rat Model (Bioresearch Communications, 2026)
Purpose: Burn injuries are a serious medical issue worldwide. In this study, Curcuma longa (CUR) loaded human amniotic membrane (HAM) gel was formulated to find an effective treatment for burn wounds with a faster healing rate and cost-effectiveness. Methodology: Physicochemical evaluation of the gel formulations was carried out through visual examination, assessing factors such as consistency, homogeneity, pH, FTIR, NMR analysis, and brine shrimp lethality test. To determine the burn wound healing efficacy, 20 female Wistar rats with 150-180g body weight were randomly divided into five groups: negative control, HAM, CUR, HAM+CUR and positive control. Burns were created and then treated with respective gels. Major findings: All gel formulations were essentially homogeneous and had good consistency with a pH between 6.68 and 6.80. FTIR and NMR studies supported the presence of collagen and skin irritation study displayed no edema or erythema after 7 days of topical application. After 16 days of treatment, the HAM+CUR group showed superiority (94.31±2.24 %) in burn wound healing, which was statistically the most significant compared to the control group (P